(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper investigated the climatic change of Gombe State metropolis from 2004 to 2014. Data were collected from Gombe State meteoroligical center, Gombe State News Bulletin, and Meteorological unit of Gombe State International Airport. Correlaion was carried out between the meteorological parameters and the years. The data was organized and analysed using Spearson correlation coefficient and ANOVA ananlysis. The paper hereby suggests that the effect of climate change to humanity can be controlled or alleviated if concrete steps that are environmentally friendly are taken.